Assessing willingness to pay for constructing septic tanks in rural Vietnam - Minh, H.V.; Hung Nguyen-Viet (2012)
The coverage of improved sanitation in Vietnam is still low, especially in rural areas. As a result, water-borne diseases remain key threats to public health. While the government has committed itself to increasing the proportion of people with access to improved sanitation, it cannot afford to subsidise sanitation for the entire population. Thus, improving rural sanitation continues to rely heavily on financial contributions from household-level private users, which depend on their willingness to pay (WTP) for such services. Knowing people’s WTP is crucial when assessing the economic viability of projects, setting fees, evaluating policy alternatives, gauging financial sustainability, and designing socially equitable subsidies. However, such information on household-level demand is scarce to non-existent in Vietnam. We assessed the WTP for septic tanks among the rural population in Vietnam and identified the some factors that influence the level of WTP. The study was conducted in Hanam province, in northern Vietnam. Researchers randomly selected and surveyed 600 households, conducting personal interviews with the main breadwinners or decision-makers in each. Contingent valuation was used to obtain relevant economic data. This method consists in asking individuals how much they would be willing to pay for a change to the quantity or quality (or both) of a particular commodity. We found that 63% of the studied households were willing to pay for construction of a septic tank. The average WTP level was VND 16 million (US$ 800), which amounts to about 15% of the households’ annual disposable income. Economic hardship was found to be the major reason for not installing a sanitary latrine. Health, cleanliness, and prestige were found to be three major motivating factors for constructing septic tanks. Regression analysis showed that the odds for spending money on improved sanitation services were higher in households with better income, as well as in households whose head had better knowledge of sanitation.